ITHQAN MAHARAT AL-LUGHAH AL-'ARABIYAH MIN KHILAL TADRIS AL-NAHW - Nasution, Sahkholid (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2016)
In some cases learning Nahwu was only stopped at the level of theory, yet its practice is still neglected. So many of the students mastered many nahwu theories but did not balance with the competence in listening, speaking, reading and writing in Arabic. It is true that learning Arabic is encouraged by nahwu, but the extent to which the model of Nahwu supports the language acquisition is questionable. Descriptive qualitative method was applied to deal with this research. The result showed that to master Arabic language through learning Nahwu, teachers should use al-Nahwu al-Wazhifi. Beside, they also can use this type of al-Nahwu al-'Ilmiy, giving examples of applicative and functional to complement existing examples in the book of al-Nahwu al-'Ilmi. In addition, because the books